A Review of Treatments for Iliotibial Band Syndrome in the Athletic Population. (2nd October 2013) - Beals, Corey; Flanigan, David
Abstract : Iliotibial band syndrome (ITBS) is a common injury in runners and other long distance athletes with the best management options not clearly established. This review outlines both the conservative and surgical options for the treatment of iliotibial band syndrome in the athletic population. Ten studies met the inclusion criteria by focusing on the athletic population in their discussion of the treatment for iliotibial band syndrome, both conservative and surgical. Conservative management consisting of a combination of rest (2–6 weeks), stretching, pain management, and modification of running habits produced a 44% complete cure rate, with return to sport at 8 weeks and a 91.7% cure rate with return to sport at 6 months after injury. Surgical therapy, often only used for refractory cases, consisted of excision or release of the pathologic distal portion of the iliotibial band or bursectomy. Those studies focusing on the excision or release of the pathologic distal portion of the iliotibial band showed a 100% return to sport rate at both 7 weeks and 3 months after injury. Despite many options for both surgical and conservative treatment, there has yet to be consensus on one standard of care. Certain treatments, both conservative and surgical, in our review are shown to be more effective than others; however, further research is needed to delineate the true pathophysiology of iliotibial band syndrome in athletes, as well as the optimal treatment regimen.